Education for Sustainable Consumption and Production (ESCP) curriculum and teaching guide for secondary education - Abdullah, Sabrina J. Ho (Universiti Putra Malaysia Press, 2018)
This book details the curriculum content for ESCP accompanied by teaching and learning modules that the teacher could use in classroom activities.